\(α\)-Klotho and Catalase: Role in Pathogenesis of Essential Hypertension - Pathare, Gauri; Raju, Sunila; Mashru, Manoj; Shah, Vinod; Shalia, Kavita (Disease and Health: Research Developments Vol. 1, 2024)
Essential hypertension is a growing global burden. One of the main risk factors for its development is oxidative stress. The levels of reactive oxygen species (ROS) are elevated in the hypertensive vasculature. Indeed, oxidative stress-induced vascular aging is observed in hypertension. Over the past decades, the anti-aging protein \(α\)-Klotho has emerged as an inhibitor of oxidative stress at cellular level. The humoral action of \(α\)-Klotho involves inhibition of the insulin-IGF-1/PI3K/AKT signalling. Forkhead box-O (FOXO) proteins, which are transcriptional regulators of antioxidative enzymes such as superoxide dismutases and Catalase, are the downstream targets of insulin-IGF-1/PI3K/AKT signalling. \(α\)-Klotho ameliorates oxidative stress by inhibiting the insulin-IGF-1/FOXO-dependent deactivation of antioxidative enzymes. The present study investigated the association between \(α\)-Klotho and Catalase in essential hypertension. The study aimed at determining \(α\)-Klotho and Catalase gene expression and Catalase activity in peripheral blood mononuclear cells (PBMCs) of essential hypertensive patients as compared to those of normotensive healthy controls in the Indian population. Forty-eight hypertensive patients and 48 age-, sex-, and BMI-matched controls were recruited. Gene expression was evaluated by quantitative Real-Time PCR. Catalase activity in PBMCs and soluble \(α\)-Klotho levels in serum were detected using Enzyme-Linked Immunosorbent Assay. Gene expression of \(α\)-Klotho and FOXO1 were significantly lower (p<0.001 and p=0.002, respectively) in patients as compared to that in controls. Catalase expression was also low in hypertensive patients but did not reach statistical significance. However, there was a strong positive correlation between \(Δ\)Ct-based gene expression of \(α\)-Klotho and Catalase in patients (p<0.001) as well as controls (p=0.008). Positive correlation was also observed between gene expression of FOXO1 and that of \(α\)-Klotho (p=0.006) and Catalase (p=0.001) in hypertensive group. Catalase activity in patients was significantly lower (p<0.001) compared to that in controls and positively correlated with soluble \(α\)-Klotho levels (rs=0.32, p=0.027), which were also 30.2% lower (p<0.001) in the patient group. Thus, the present study found that the soluble levels and gene expression of anti-aging protein \(α\)-Klotho were low in hypertensive patients. \(α\)-Klotho may influence Catalase expression in essential hypertension through its effect on FOXO1. \(α\)-Klotho and Catalase may have therapeutic potential in the treatment of essential hypertension and other oxidative stress-related diseases.